Long-Term Pediatric Ventricular Assist Device Therapy: A Case Report of 2100+ Days of Support. Issue 1 (January 2018) - Purkey, Neha J.; Lin, Aileen; Murray, Jenna M.; Gowen, Maryalice; Shuttleworth, Paul; Maeda, Katsuhide; Almond, Christopher S.; Rosenthal, David N.; Chen, Sharon
Abstract : Ventricular assist devices (VADs) have been placed as destination therapy in adults for more than 20 years, but have only recently been considered an option in a subset of pediatric patients. A 2016 report from the Pediatric Interagency Registry for Mechanical Circulatory Support revealed only eight pediatric patients implanted with a VAD as destination therapy. Herein, we report the case of an adolescent male with Becker muscular dystrophy who underwent VAD placement in 2011 as bridge to candidacy. He subsequently decided to remain as destination therapy and so far has accrued more than 2100 days on VAD support, the longest duration of pediatric VAD support reported in the literature to date.